Hyperleukocytosis in Solid Tumors: a Rare Paraneoplastic Syndrome Associated with Poor Prognosis - Ferrão, J (2021)
Hematological paraneoplastic syndromes are fairly uncommon. While mild leukocytosis in solid tumors is well reported, white blood cell (WBC) count over 50,000 u/L, described as paraneoplastic leukemoid reaction (PLR), is not. Indeed, when found, it is usually associated with a higher burden of disease, tumor activity and worse clinical outcomes. We report the case of a challenging and burdensome diagnosis of a presumptive hematological paraneoplastic syndrome in a patient with a locally advanced lung cancer admitted in the Internal Medicine ward. After the end of chemotherapy, clinical and laboratory benefit was observed; however, the aggressive course of the disease became clear, with progression and downhill course that was unresponsive to treatment.